The Role of Splanchnic Congestion and the Intestinal Microenvironment in the Pathogenesis of Advanced Heart Failure - Polsinelli, Vincenzo B. (Curr Opin Support Palliat Care, 2019)
PURPOSE OF REVIEW: Right-sided heart failure (HF), which is often present in the setting of advanced HF, is associated with cardiac cachexia, the cardiorenal syndrome, and adverse outcomes. Improved understanding of venous congestion of the splanchnic circulation, which may play a key role in the pathogenesis of right-sided HF, could lead to novel therapeutics to ameliorate HF. Here we provide an overview of right-sided HF, splanchnic hemodynamics, fluid homeostasis, and the intestinal microenvironment. We review recent literature to describe pathophysiologic mechanisms and possible therapeutics. RECENT FINDINGS: Several possible mechanisms centered around upregulation of sodium-hydrogen exchanger-3 (NHE3) may form a causal link between right ventricular (RV) dysfunction, splanchnic congestion, and worsening HF. These include: (1) an anaerobic environment in enterocytes, resulting in reduced intracellular pH; (2) increased sodium absorption by the gut via NHE3; (3) decreased pH at the intestinal brush border thus altering the gut microbiome profile; (4) increased bacterial synthesis of trimethylamine N-oxide; and (5) decreased bacterial synthesis of short-chain fatty acids causing abnormal intestinal barrier function. SUMMARY: Splanchnic congestion in the setting of right-sided HF may serve an important role in the pathogenesis of advanced HF, and further exploration of these mechanisms may lead to new therapeutic advances.